Survey of medium access control schemes for inter-vehicle communications. (November 2017) - Torabi, Nasser; Ghahfarokhi, Behrouz Shahgholi
Highlights: The paper presents a novel inclusive classification of strategies for designing V2V MAC schemes. The paper compares V2V MAC schemes with respect to their compatibility with standards. The paper compares famous V2V MAC schemes from QoS and performance points of view. Abstract: Currently, Vehicular Ad-hoc Networks (VANETs) are attracting a lot of attention due to their favorable applications. VANETs are the key to providing safety and efficiency on the roads. The vehicles can communicate with other vehicles to inform the ongoing status of the traffic flow or critical situations like accidents. However, this would entail a reliable and efficient Medium Access Control (MAC) protocol. Due to the high speed of the nodes, the frequent changes in network topology, and particularly the lack of an infrastructure, the design of the MAC for vehicular communications turns into a more challenging task. A lot of research works has been conducted to overwhelm the vehicular MAC problems regarding Quality of Service (QoS) requirements of both safety and non-safety applications covering both Vehicle-to-Infrastructure (V2I) and Vehicle-to-Vehicle (V2V) communications. Recently, a significant number of MAC schemes has been proposed for V2V communications. In this paper, for future studies to be more effective, the outstanding proposed V2V MAC schemes are intended to come under review. Moreover, V2V MAC design approaches are discussed and a qualitative comparison is provided. A novel classification of V2V MAC schemes is then presented, and the characteristics of these schemes along with their strengths and weaknesses are studied. Finally, a comparative summary is given and some open challenges regarding the design of V2V MAC schemes are discussed. Graphical abstract: